2020
DOI: 10.1159/000511390
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis Is an Option for Acute Kidney Injury Management in Patients with COVID-19

Abstract: In December 2019, cases of acute respiratory illness of unknown origin were reported in Wuhan, China. The disease is caused by “severe acute respiratory syndrome coronavirus 2”. After identifying severe lung damage, injury to other organs, such as the kidney, has been identified. Peritoneal dialysis is a renal replacement therapy (RRT) and is at least as effective as other extracorporeal therapy options, with significant cost-effective advantages. However, this strategy is rarely used for the management of acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The socioeconomic burden of RRT is high, since conventional HD is rather costly for healthcare providers, with substantial differences in funds available per capita across different countries (58). As alternative to HD (8), PD is a well-established and viable option for home RRT, which minimizes potential virus exposure and the associated health risks (10)(11)(12)(13)(14)(15). However, its long-term use is limited due to the decline in peritoneal ultrafiltration that typically occurs 2-4 years after initiation of PD (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The socioeconomic burden of RRT is high, since conventional HD is rather costly for healthcare providers, with substantial differences in funds available per capita across different countries (58). As alternative to HD (8), PD is a well-established and viable option for home RRT, which minimizes potential virus exposure and the associated health risks (10)(11)(12)(13)(14)(15). However, its long-term use is limited due to the decline in peritoneal ultrafiltration that typically occurs 2-4 years after initiation of PD (22).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with kidney failure requiring regular renal replacement therapy (RRT) are at particular risk of infection and Coronavirus-induced disease 2019 (COVID-19) (5)(6)(7). In addition to commonly used hemodialysis (HD) (Figure 1A), peritoneal dialysis (PD) (Figure 1B) is a valuable cost-effective 'home-care' RRT, which combines patients' independence from HD centres with self-isolation, and thus is of particular interest during the COVID-19 pandemic (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated susceptibility to infection in patients undergoing PD, although the reported cases are less frequent than in hemodialyzed patients [ 235 ]. However, PD could represent a more practical and safer KRT method for CKD patients, considering a home-safer option during the pandemic crisis [ 236 ]. In this sense, a recent cohort population study of PD patients pointed out that this KRT does not increase the risk of infection for SARS-CoV-2.…”
Section: Covid-19 In Ckd Patients Under Krt and In Mesotheliummentioning
confidence: 99%
“…During the height of the pandemic, some RRT modalities were insufficient, forcing medical centers to diversify the RRT modalities offered. In regions of low- and lower-middle-income countries, peritoneal dialysis (PD) during the COVID-19 pandemic is an alternative to be considered [5, 6]. In Mexico, PD is the first alternative and the main RRT therapy, especially within health institutions.…”
Section: Introductionmentioning
confidence: 99%